1996
DOI: 10.1148/radiology.199.3.8637978
|View full text |Cite
|
Sign up to set email alerts
|

Acute mesenteric ischemia: diagnosis with contrast-enhanced CT.

Abstract: Dynamic, contrast-enhanced CT is a valuable tool in the diagnosis of and determination of prognosis in acute mesenteric ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
2
19

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 272 publications
(165 citation statements)
references
References 0 publications
9
135
2
19
Order By: Relevance
“…While traditional CT imaging has improved the diagnosis of many abdominal diseases, it has been shown to have a sensitivity of only 64% for the diagnosis of mesenteric ischemia. 14 Because of the ability of M.D.CT-CTA to visually represent arterial anatomy and perfusion, it may represent a great improvement over single-detector CT in imaging this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While traditional CT imaging has improved the diagnosis of many abdominal diseases, it has been shown to have a sensitivity of only 64% for the diagnosis of mesenteric ischemia. 14 Because of the ability of M.D.CT-CTA to visually represent arterial anatomy and perfusion, it may represent a great improvement over single-detector CT in imaging this disease.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that spiral CT demonstrated a sensitivity and specificity of 64% and 92%, respectively, for diagnosing mesenteric ischemia. 14 Multidetector CT, combining multiple rows of detectors and faster gantry rotation with narrow collimation, increases scanning speed and virtually eliminates motion and respiratory artifact. These factors allow for improved visualization of the small-bowel wall and distal branches of the mesenteric vessels.…”
mentioning
confidence: 99%
“…Radiographs can demonstrate thumbprinting due to bowel wall edema or intramural hemorrhage; in more advanced stages, pneumatosis or portal venous gas, the latter being a poor prognostic sign, can be present. CT may show ascites, dilated bowel, mural thickening, or abnormal wall enhancement as well as abnormalities in the mesentery including edema and vessel engorgement (34). However, the features of ischemic bowel are not specific for SLE and vary depending on the duration of the ischemia.…”
Section: Bowelmentioning
confidence: 99%
“…Imaging studies reveal thrombosis in the mesenteric veins, establishing a definitive diagnosis of mesenteric venous thrombosis. Computed Tomography with contrast is the initial test of choice and is diagnostic in up to 90% of cases [12]. If this fails to make a diagnosis, and there is high clinical suspicion of thrombosis, CT angiography with delayed imaging or Magnetic resonance angiography may be done.…”
Section: Discussionmentioning
confidence: 99%